A New Perspective at Comprehensiveness of Islamic Education Theory with Regard to Concept of Silence in Jurisprudential and Legal Sources - Seyed Nooruddin Heidari Manesh (Comparative Education Society of Iran ( CESIR), 2021)
The changes of the last half century in the world, influenced by new technologies, have posed new issues and challenges to religious and educational systems. In this situation, in Iran “educational jurisprudence” emphasizes the theory of "comprehensiveness of Islamic education" through extending the theory of "comprehensiveness of Islam" to the field of education. The purpose of this study is to critique the “comprehensiveness of Islamic education theory” with regard to the concept of silence in jurisprudential and legal sources. While the method of study is comparative, library method and conceptual-religious method were used to collect and analyze data respectively. The research findings showed that although there are differences between jurists regarding the theory of the Shari'a silence in jurisprudence, but the proposition of "accepting the silence of Shari'a relatively" by some jurists - which is an intermediate view - can indicate the rejection of comprehensiveness of Islamic education theory. Also, the findings indicate that the main discussion of the jurists is about possibility of stabilizing or changing the decrees that already existed, and there has been less discussion about new issues of contemporary world - for which there is no previous Islamic rules. In a general conclusion, it can be said that acceptance of comprehensiveness of Islam does not necessarily mean the comprehensiveness of "Islamic education" and denying this comprehensiveness can reduce the heavy responsibility of those who believe in this theory.